Selective degradation of organic micropollutants by activation of peroxymonosulfate by Se@NC: Role of Se doping and nonradical pathway mechanism - Chai, Yandong; Dai, Hongling; Zhan, Peng; Liu, Zhaochen; Huang, Zhen; Tan, Chaoqun; Hu, Fengping; Xu, Xing; Peng, Xiaoming (Journal of hazardous materials, 2023)
In this study, Se@NC-x decorated with Se was successfully prepared via two-step calcination with zeolitic imidazole framework (ZIF) as a precursor. Mechanistic studies show that PMS would be adsorbed onto the surface of Se@NC-900 to form an active complex (Se@NC-900/PMS*), and the active Se@NC-900/PMS* could oxidize phenol by the rapid decomposition of PMS. Specifically, electrons are extracted by Se@NC-900/PMS* and then transferred to the surface of Se@NC-900, which can trigger the degradation of phenol. Notably, it is found that the local charge redistribution caused by the doping of Se can activate the catalytic potential of the intrinsically inert carbon skeleton through density flooding theory (DFT) calculations. The XLogP, ΔE, VIP, and ELUMO (Se@NC/PMS)-HOMO (pollutants) and degradation rate constants of different micropollutants were correlated well linearly. This indicates that the Se@NC-900/PMS system has a great selectivity for the degradation of pollutants. Overall, these findings not only illustrate the role of Se in tuning the electronic structure of Se@NC-x to enhance the activation of PMS, but also bridge the gap in our knowledge about the physicochemical properties and degradation performance of Se@NC catalysts. [Display omitted] •Se@NC-x was used as catalysts to activate the PMS for micropollutants degradation.•Se@NC-x shows its universality and stability in the PMS-based oxidation process.•The Se@NC-x /PMS system catalytic mechanisms were elucidated.•The relation of parameters and degradation rate constants are correlated linearly.